PERSEPSI MASYARAKAT TERHADAP CULTURE FASHION SNEAKERS KOMUNITAS INDONESIA SNEAKER TEAM - Arif Kurnia Yahya (Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to find out how the audience perceives Culture Fashion Sneakers in the Indonesian Sneaker Team community and the containers displayed in society and sneakerheads now in Indonesia, especially in the Indonesian Sneaker Team community. With this research establishing a constructivist paradigm with the phenomenological method, interviews were used to gain a deeper understanding of the experiences and perceptions of the informants on the research topic. The results of this study indicate that the community has a positive view of the fashion sneakers culture. Fashion sneakers are considered a statement of personal style and a source of confidence. Social identity is also found through the use of sneakers, where community members feel connected and support one another. The culture of fashion sneakers is also considered as a means of self-expression and a dynamic lifestyle. This research also reveals the importance of the Indonesian Sneaker Team Community as a social space for sneakers fans. This community provides an opportunity to share knowledge, experiences, and shoe collections. In addition, this community plays an important role in shaping and strengthening the social identity of its members as sneakerheads.